simplify(3-√5) (3+√5)
Answers
Answered by
0
Answer:
4
Step-by-step explanation:
3^2-√5^2
since
a square + b square = (a+b)(a-b)
=9-5
=4 ans
Answered by
1
4
Step-by-step explanation:
(3 - √5) (3 + √5)
=> (3)² - (√5)²
[using the formula (a - b) (a + b) = a² - b², here a = 3 and b = √5]
=> 3² - √5²
=> 9 - 5
=> 4
Hence (3 - √5) (3 + √5) = 4
hope it helps.
Similar questions
Social Sciences,
2 months ago
India Languages,
2 months ago
Math,
3 months ago
Business Studies,
11 months ago
Math,
11 months ago